RESPONS KONSENTRASI PUPUK ORGANIK CAIR URIN SAPI DAN PGPR (Plant Growth Promoting Rhizobacteria) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Alifia Herwinda Irawan; Andi Apriany Fatmawaty; Nuniek Hermita; Kartina A.M (BPFP Universitas Bengkulu, 2023)
[ENHANCING THE GROWTH AND YIELD OF PAKCHOY THROUGH THE APPLICATION OF COW URINE LIQUID ORGANIC FERTILIZER AND PGPR AT VARYING CONCENTRATIONS]. The employment of plant growth-promoting rhizobacteria (PGPR) has demonstrated potential as a promising method in the adoption of sustainable agricultural practices. This study aimed to determine the developmental and productive aspects of pakcoy under varying exposures to Plant Growth Promoting Rhizobacteria (PGPR) and liquid organic fertilizer derived from cow urine. Conducted experimentally from March to May 2023, the research employed a randomized block method with three replications and two factors. The liquid organic fertilizer from cow urine was administered at four levels: control, 20 mL/L, 30 mL/L, and 40 mL/L. Simultaneously, PGPR was applied at four levels: control, 15 mL/L, 20 mL/L, and 25 mL/L. Results indicated that cow urine significantly influenced parameters such as plant height at 3 WAP (19.98 cm), 4 WAP (22.92 cm), and 5 WAP (23.45 cm), as well as the number of leaves and root length. PGPR, on the other hand, exhibited notable effects on plant height at 4 WAP (24.00 cm) and 5 WAP (23.94 cm), number of leaves, root length, plant fresh weight, and plant dry weight. Notably, the interaction between PGPR and cow urine affected pakchoy growth components, particularly in plant height at 4 WAP and 5 WAP